NEUROTICISM BIASES ASSESSMENT OF SUBJECTIVE MEMORY IMPAIRMENT IN WOMEN. (11th November 2018) - Whitaker, E; Hill, N; Mogle, J; Bhang, I; Bhargava, S
Abstract: Subjective memory impairment (SMI) is common in the years prior to objectively identifiable cognitive deficit. Personality traits, specifically neuroticism, may impact SMI reporting as some assessment items may induce bias, such as when presented to individuals higher in neuroticism who are more sensitive to social threat. This is of particular interest in women, as they have higher levels of neuroticism as well as a unique risk profile for cognitive decline. We examined whether neuroticism influenced SMI and the consistency of these effects across different SMI assessment items. Women (n=1, 132; Mage=52.71; SD=13.99) completed the Midlife Development Inventory neuroticism subscale and two SMI items: a self-comparison, and an age-anchored comparison. Higher neuroticism was associated with poorer ratings on both SMI items, as well as increased consistency in responses to the two items (i.e. closer ratings between the two items). Higher neuroticism in women may bias SMI assessment and reduce the sensitivity of assessment tools.